In silico nanotoxicology: The computational biology state of art for nanomaterial safety assessments - Suresh K. Verma; Aditya Nandi; Faizan Zarreen Simnani; Dibyangshee Singh; Adrija Sinha; Shaikh Sheeran Naser; Jyotirmayee Sahoo; Sudakshya S. Lenka; Pritam Kumar Panda; Ateet Dutt; Nagendra Kumar Kaushik; Deobrat Singh; et al. (Materials & Design, 2023)
In recent decade, nanotechnology has got an extensive advancement in terms of production and application of nanomaterials. With the advancement, concern has risen for their biomedical and ecological safety, provoking a detailed analysis of the safety assement. Numerous experimental and computational approach has been developed to accomplish the goal of safety assessment of nanomaterials leading to orgin of interdisciplinary fields like nanoinformatics. Nanoinformatics has accomplished significant strides with the development of several modeling frameworks, data platforms, knowledge infrastructures, and in silico tools for risk assessment forecasts of nanomaterials. This review is an attemption to decipher and establish the bridge between the two emerging scientific arenas that includes computational modeling and nanotoxicity. We have reviewed the recent informations to uncover the link between the computational toxicology and nanotoxicology in terms of biomedical and ecological applications. In addition to the details about nanomaterials interaction with the biological system, this article offers a concise evaluation of recent developments in the various nanoinformatics domains. In detail, the computational tools like molecular docking, QSAR, etc. for the prediction of nanotoxicity here have been described. Moreover, techniques like molecular dynamics simulations used for experimental data collection and their translation to standard computational formats are explored.